Isoform CYP1A2, as a part of the cytochrome P450 superfamily - Y. G. Novickaya; V. P. Zherdev; A. O. Viglinskaya; A. A. Litvin (Фармакокинетика и Фармакодинамика)
The role of cytochrome P450 isoforms CYP1A2 and in the metabolism of caffeine is described. Caffeine pharmacokinetics data in humans and laboratory animals are presented. Examples of drug-drug interactions of cubstrate marker caffeine with different drugs are given.